2014
DOI: 10.3109/01443615.2014.896884
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a gonadotrophin-releasing hormone agonist prior to myomectomy – comparison of twice- vs thrice-monthly doses and a control group

Abstract: The aim of this randomised prospective study was to investigate the impact of preoperative gonadotrophin-releasing hormone agonist (GnRHa) compared with a control group with myomectomy. A total of 36 women (n = 36, group 1) with fibroids were randomised to receive either two monthly doses (n = 18/36, group 1a) or three monthly doses of goserelin (n = 18/36, group 1b) prior to myomectomy. The 32 women who received no treatment (group 2) comprised the controls. All patients had similar demographic features. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Detailed information for each included study on the different GnRHa preparations, their routes of administration or duration of treatment can be found in Table 1 . In two studies in the laparotomic group, comparisons were made between leuprolin 3.75mg, leuprolin 7.5mg and no pre-treatment [ 28 ] and between goserelin 3.6mg two doses every four weeks, goserelin 3.6mg three doses every four weeks and no pre-treatment [ 26 ]. We chose to use the data from the leuprolin 3.75 mg and two doses goserelin 3.6mg every four weeks, since these are more comparable to the other pre-treatment schedules in our analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information for each included study on the different GnRHa preparations, their routes of administration or duration of treatment can be found in Table 1 . In two studies in the laparotomic group, comparisons were made between leuprolin 3.75mg, leuprolin 7.5mg and no pre-treatment [ 28 ] and between goserelin 3.6mg two doses every four weeks, goserelin 3.6mg three doses every four weeks and no pre-treatment [ 26 ]. We chose to use the data from the leuprolin 3.75 mg and two doses goserelin 3.6mg every four weeks, since these are more comparable to the other pre-treatment schedules in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported on difficulty of the surgery (n = 147). A cohort study by Bassaw et al [ 26 ] assessed difficulty in enucleating the fibroids by asking surgeon whether the enucleation was considered difficult or not. No definition of ‘difficult’ was given.…”
Section: Resultsmentioning
confidence: 99%
“…For hysteroscopic myomectomies, surgeons evaluated hysteroscopic visualization (excellent [score = 3]; good [2]; or satisfactory, poor, or very poor [1]), relationship to the myometrium (well delineated [3]; well delineated in some areas, poor in others [2]; or poorly delineated throughout [1]), extrusion into the cavity during the procedure (yes [2] or no [1]), distension fluid deficit (<250 mL [3], 250-500 mL [2], or >500 mL [1]), estimated blood loss (<50 mL [3], 50-100 mL [2], or >100 mL [1]), and overall ease of the procedure compared with other similar cases (easier [3], routine [2], or more difficult [1]). The overall hysteroscopic surgical experience score was determined by summing the scores for each subscale for a total of 6 to 17, with higher scores indicating a better surgical experience.…”
Section: Assessmentsmentioning
confidence: 99%
“…The overall hysteroscopic surgical experience score was determined by summing the scores for each subscale for a total of 6 to 17, with higher scores indicating a better surgical experience. Similarly, for laparotomic/ laparoscopic myomectomies, surgeons evaluated ease of delineating surgical planes between the myoma and the myometrium (very easy [5], easy [4], routine [3], difficult [2], or extremely difficult [1]), ease of myoma separation from the surrounding myometrium (very easy [5], easy [4], routine [3], difficult [2], or extremely difficult [1]), estimated blood loss (<100 mL [4], 100-250 mL [3], 250-500 mL [2], or >500 mL [1]), and overall ease of the procedure compared with other similar cases (easier [6], routine [4], or more difficult [1]). The laparotomic/laparoscopic surgical experience score was calculated by summing the scores for each subscale for a total of 4 to 20, with higher scores indicating a better surgical experience.…”
Section: Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation